Estimates the Evolution of G8P[8] Rotaviruses in Thailand during 2012 - 2014 - Chutoam, Palatip; Intamaso, Uraiwan (Trends in Sciences, 2022)
Point mutation and abrupt changes of segmented genomes of rotavirus group A (RVAs) from mixed infection are critical factors for generating genetically divergent strains. Our preceding study of rotavirus infections in 2012 - 2014 in Thailand indicated the high prevalence of G8P[8] strains. This study aimed to identify the origin of each segment of the genome of these G8P[8] RVA strains by using phylogenetic analysis. All gene segments from the 5 selected G8P[8] were sequenced partially and aligned with locally circulating rotavirus strains to estimate the phylogenic relationship. Based on the genome's constellation of the genome, these 5 strains’ genetic backgrounds possessed genotype constellation 2 or called the DS-1-like genotype. Ten genes, except for VP6, were clustered within the same phylogenic tree of the cognate genes of Thai circulating G8P[8]strains isolated between 2013 - 2014. Their 5 genes VP2, VP3, NSP1, NSP3, and NSP5, also exhibited high nucleotide similarities with the first unusual Japanese DS-1-like strains G1P[8] NT004. Besides, the VP4 shared a high nucleotide sequence similarity with the cognate gene of circulating Thai human G1P[8] Wa-like and G1P[8] NT004. However, the remaining 4 gene segments (VP1, VP7, NSP2, and NSP4) were clustered with other human or animal RVA strains within the same monophyletic. All of these G8P[8] strains shown to be an intragenogroup reassortment. Thus, characterization of the genomes is crucial to monitor the evolutionary dynamics and relationships of co-circulating RVAs in predicting the effectiveness of current vaccines and future vaccine development strategies. HIGHLIGHTS G8P[8] strains’ genetic backgrounds possessed genotype constellation 2 ( DS-1-like genotype) G8P[8] strains might originate from a sequential process of multiple reassortment events involving intra-genogroups from humans and animal species Ten genes, except for VP6, were clustered within the same phylogenic tree of the cognate genes of Thai circulating G8P[8]strains isolated between 2013 - 2014 GRAPHICAL ABSTRACT